2013
DOI: 10.1038/ncomms3568
|View full text |Cite
|
Sign up to set email alerts
|

Distinct charge dynamics in battery electrodes revealed by in situ and operando soft X-ray spectroscopy

Abstract: Developing high-performance batteries relies on material breakthroughs. During the past few years, various in situ characterization tools have been developed and have become indispensible in studying and the eventual optimization of battery materials. However, soft X-ray spectroscopy, one of the most sensitive probes of electronic states, has been mainly limited to ex situ experiments for battery research. Here we achieve in situ and operando soft X-ray absorption spectroscopy of lithium-ion battery cathodes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
236
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(247 citation statements)
references
References 34 publications
10
236
0
1
Order By: Relevance
“…Differently, here we found inhomogeneity in the entire electrode with hard X-rays penetrating through the electrode. Using direct imaging technology, our result also confirms the recent charge dynamic study in a LiFePO 4 electrode with soft X-ray spectroscopy that observed inhomogeneity in polymer electrolyte electrodes with low ion conductivity 36 . In our work, the use of low active material loading and liquid electrolyte is supposed to enhance the ionic and electron conductivity.…”
Section: Discussionsupporting
confidence: 79%
“…Differently, here we found inhomogeneity in the entire electrode with hard X-rays penetrating through the electrode. Using direct imaging technology, our result also confirms the recent charge dynamic study in a LiFePO 4 electrode with soft X-ray spectroscopy that observed inhomogeneity in polymer electrolyte electrodes with low ion conductivity 36 . In our work, the use of low active material loading and liquid electrolyte is supposed to enhance the ionic and electron conductivity.…”
Section: Discussionsupporting
confidence: 79%
“…34,35 In addition, by recording NEXAFS spectra with different detection modes such as total electron yield (TEY) and total fluorescence yield (TFY), different probing depths can be achieved. The TEY mode probes a depth of B5 nm, whereas the TFY mode probes a depth of B100 nm.…”
Section: Nexafs Characterization Of Sulfur Electrodesmentioning
confidence: 99%
“…During the charging (lithium deintercalation) and discharging (lithium intercalation) processes, nickel switches between Ni 2+ and Ni (2+x)+ oxidation states, where the x value is usually determined by the degree of lithium deintercalation, i.e., charging voltage cutoff in the galvanostatic or potentiostatic cycling. 12,24,31,32 At the end of discharge, the nickel oxidation state returns to Ni 2+ independent of changes in the crystal structure (Fig. 7a), so that detection of Ni 2+ in the TEY data is not proof per se of surface reconstruction to the rock salt structure.…”
mentioning
confidence: 99%